Effect of different culture media on isolation and differentiation of dendritic cells - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (WALTER DE GRUYTER GMBH, 2015)
Objective: Dendritic cells (DCs) are members of the mammalian immune system and are considered to be the most powerful antigen presenting cells. They are responsible for the induction of T-cells or T-cell dependent immunity and tolerance. In this study we have investigated the effect of different serum supplements on generation and yield of mature dendritic cells isolated from peripheral blood mononuclear cells. Methods: Three different serum supplements (10% Fetal Bovine Serum, 1% Human Serum Albumin and 1% autologous serum) were compared with serum-free media to identify the role and importance of serum supplements on DC cultivation. Effect of different media on maturation signs (CD40, CD80, CD86, CD209a) and cytokine release (TNF-alpha, IL-10, IL-12, IL-6) was examined. Results: DCs generated in serum-free media was similar to those of cells in medium with autologous serum. Few dendritic-like cells were observed in fetal bovine serum and human serum albumin. The effect of different media on maturation of DCs was compared phenotypically and increased expression of CD80, CD86 and CD209a identified maturation and yield of DCs. Conclusion: Our results suggest that serum free media can be used to overcome potential drawbacks associated with different serum containing supplements.
Keywords: Dendritic cells; peripheral blood mononuclear cells; serum-free media; CD209a; IL-10; IL-12; PERIPHERAL-BLOOD; LANGERHANS CELLS; IN-VITRO; HEMATOPOIETIC PROGENITORS; BONE-MARROW; T-CELLS; DC-SIGN; GENERATION; MACROPHAGES; TOLERANCE